2020
DOI: 10.1177/0046958020921070
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Media and Environmental Pollution on the Economy and Health Using a Modified Meta 2-Stage EBM Malmquist Model

Abstract: China’s pursuit of economic growth, rapid industrialization, and urbanization over the past few decades has resulted in high energy consumption, which in turn has caused serious environmental pollution problems, such as CO2 and PM2.5 emissions, the long-term exposure to which can seriously affect resident health. To resolve these air pollution problems, the Chinese government has put in place several policies to reduce air and environmental pollution. Past studies on energy and environmental efficiency have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
(142 reference statements)
0
8
0
Order By: Relevance
“…A study used a modified Malmquist meta-2-stage Epsilon-Based Measure (EBM) model to explore the relationship between economy, energy, environment, health, and media, as well as regional differences in 31 Chinese cities from 2014 to 2016. The study found that there is a gap between the eastern, central, and western technology frontiers, and variation in the healthcare stage is greater than the production stage [4].…”
Section: Introductionmentioning
confidence: 90%
“…A study used a modified Malmquist meta-2-stage Epsilon-Based Measure (EBM) model to explore the relationship between economy, energy, environment, health, and media, as well as regional differences in 31 Chinese cities from 2014 to 2016. The study found that there is a gap between the eastern, central, and western technology frontiers, and variation in the healthcare stage is greater than the production stage [4].…”
Section: Introductionmentioning
confidence: 90%
“…Mykhalovskiy et al, 2004 give thoughts, reviews, and evaluations to assist in developing more comprehensive social scientific research of EBM [21]. Li et al, 2020 utilized a modified meta-two-stage EBM Malmquist approach to investigate regional disparities in thirty-one Chinese cities' economies, energies, environments, health, and media during 2014-2016 [22]. A quantitative method was used by Rusli et al to evaluate the logistics sector in Malaysia before and after the COVID-19 pandemic by comparing the sector's effectiveness and efficacy using the EBM and Malmquist index approaches.…”
Section: Related Workmentioning
confidence: 99%
“…Economic development stage variables: Regarding input indicators, with reference to previous studies (Li et al, 2019a;Li et al, 2019b;He et al, 2020;Li et al, 2020), we chose to use labor and energy consumption as input indicators. However, this paper cannot include fixed assets as input indicators due to limitations in data availability.…”
Section: Variables Selectionmentioning
confidence: 99%